Adaptive Tourism Policy-Making in the Face of Natural Disasters: A Case Study of Mount Merapi, Indonesia - Hoirunnisya Hoirunnisya; Gerry Katon Mahendra (Journal of Social and Policy Issues, 2025)
This study aims to analyze how natural disasters, particularly the eruption of Mount Merapi, impact policy-making in the natural tourism sector of Sleman Regency. Using qualitative approach, data were collected through interviews, observation, documentation, and literature review. The results show that the impacts of the Merapi disaster, such as environmental damage, socio-economic changes, loss of life, and economic paralysis, lead to the development of disaster policies in the tourism sector. The policy-making process is carried out in stages, including problem identification, needs analysis, goal formulation, policy model selection, social indicator determination, and building public support. The resulting policies include the establishment of Disaster Resilient Villages/Urban Villages (Destana/Kaltana), the use of the SI PANDU MERAPI application, the installation of an Early Warning System (EWS), and the training of tourism volunteers. These policies have increased community preparedness, restored tourist confidence, and boosted post-eruption visits. However, some impacts, such as damage to vehicle engines due to volcanic ash, have not yet been addressed through specific government policies. This study concludes that risk-based and participatory mitigation policies can strengthen the resilience of the tourism sector. However, they need to be complemented by more comprehensive policies to address all disaster impacts.